Mixed Fermentations of Yeasts and Lactic Acid Bacteria as Sustainable Processes to Enhance the Chemical Composition of Cider Made of Topaz and Red Topaz Apple Varieties - Paul Cristian Călugăr; Teodora Emilia Coldea; Carmen Rodica Pop; Laura Stan; Emese Gal; Floricuța Ranga; Simona Codruța Hegheș; Elena Mudura (Agronomy, 2023)
This study examined the effect of simultaneous fermentations of Saccharomyces cerevisiae and Pichia kluyveri, Lactobacillus plantarum and Oenococcus oeni on the chemical composition of apple cider from two apple varieties—Topaz and Red Topaz. Analytical techniques (HPLC-RID, HPLC-VWD, GC/MS, GC/FID, HPLC-DAD ESI+) were employed to analyze glucides, organic acids, volatile compounds, amino acids and phenolic compounds, respectively. Statistical analysis and and PCA were conducted to assess the correlations among samples based on the compounds identified. In the mixed fermentations, such as Saccharomyces cerevisiae + Lactobacillus plantarum and Saccharomyces cerevisiae + Oenococcus oeni, the amount of lactic acid was higher compared to the other samples, thus proving the effectiveness of malolactic fermentation simultaneous to alcoholic fermentation. The fermentation of Saccharomyces cerevisiae + Pichia kluyveri resulted in the formation of greater amounts of certain volatile compounds. Moreover, the sensory analysis revealed that Saccharomyces cerevisiae + Pichia kluyveri distinguished apple-like, fruity and floral notes. This study suggests that the simultaneous inoculation of Saccharomyces and non-Saccharomyces yeasts results in a more complex-flavored cider. The mixed fermentation of yeast and lactic acid bacteria is a sustainable method given the shortened fermentation duration and can be successfully applied in the cider industry.